A Code for Public Prosecutors in the Nigerian Criminal Justice System: A Necessity or a Nuisance? (Global Journal of Human-Social Science, 2019)
The general supervisory power and control over criminal prosecution is vested in the Attorney- General of a State under section 211and in the Attorney - General of the Federation under section 174 of the 1999 Constitution of the Federal Republic of Nigeria as amended however the Nigerian Police Act and other entities such as the anti-graft agencies have powers of prosecution subject however to the power of the Attorney General Though there is an operational Code of Conduct for Prosecutors its universal reach in the country and efficiency of supervision and sanction of errant prosecutors has been a major concern for stakeholders in the administration of justice This paper examined the preserve of the prosecutors in criminal trials and analysed the Code of Conduct for Prosecutors CCP in Nigeria drawing from the provisions the Prosecutors Code of selected jurisdictions
Keywords: prosecutor; code of conduct; police; attorney- general; criminal justice system; fair trial; accused